Tinjauan Ekonomi Syariah tentang Proyeksi Penerimaan dan Penggunaan Wakaf pada Wakaf Daarut Tauhiid - Camila Afiyanti; M. Roji Iskandar; Ifa Hanifia Senjiati (UNISBA Press, 2022)
Abstract. Based on the results of preliminary observations, that the nominal amount of revenue, use and balance in Daarut Tauhiid waqf management activities in 2015-2019 shows a fluctuating development trend. Overall data on the number of receipts showed an increase until 2018, and in 2019 showed a declining trend. The usage graph is relatively stable and shows an increasing development every year. In contrast to receipts and usage charts, charts for balances show unpredicable (unpredictable) developments. The balance in 2015 to 2016 showed a decrease, then rose to the following years and reached the highest curve in 2018. The balance for 2019 showed a very significant decline.The type of research used is descriptive method with a qualitative approach. The data needed from this study are primary data (interviews with waqf managers) and secondary data (recap documents of DT Waqf activity reports in 2015-2019). As for managing data, the author uses a qualitative research type that is descriptive analysis. In accordance with the title of the study, the analysis used is